EVERYDAY STORIES AND UNTOLD TALES OF INFERTILITY: A LITERARY EXAMINATION OF AYOBAMI ADEBAYO'S STAY WITH ME - Yeboah, Philomena Ama Okyeso; Mohammed, Mariam; Freitas, Philip Kwame; Otoo, Paul (International Journal of Humanity Studies (IJHS), 2024)
Matters concerning infertility mostly hinge on societal narratives. This has led to a lot of misconceptions which have had great influence in the lives of people and society at large. Several literary works have given space to issues of infertility and have highlighted pertinent issues that have received too much or little attention from society. In this paper, using a qualitative methodological approach, disturbing discoveries concerning how the issue of infertility is handled in African societies have been made from Ayobami Adebayo's Stay With Me, highlighting the fact that all accusing eyes turn to the woman when the home is void of a child and the position men assume in such instances. Leaning on the theories of feminism and masculinity, this study seeks to expose the neglected aspect of infertility by highlighting the gaps in the ways infertility issues are handled in African societies and contributing to the knowledge bank of academia.